2017
DOI: 10.3178/hrl.11.92
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of seasonal precipitation isotope variability in Indonesia

Abstract: Abstract:The few previous studies of precipitation isotopes (δ 18 O and δD) in Indonesia, based on low spatial resolution observation datasets, have found several types of patterns in their seasonal variabilities. This study conducted high spatial resolution rainfall sampling and investigated the temporal characteristics of precipitation isotope in Indonesia. Rainfall samples were collected weekly from 33 stations in Indonesia. Cluster analysis showed that Indonesia could be divided into four types based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Regional rainfall stations with isotope data demonstrate that Indonesian rainfall can be described by four groups based on seasonal isotopic variability (Belgaman et al, 2017). These four rainfall types correspond to the rainfall regions as defined by Aldrian and Dwi Susanto (2003).…”
Section: Controls On Rainfall 18 O At Tangga Cavementioning
confidence: 68%
See 1 more Smart Citation
“…Regional rainfall stations with isotope data demonstrate that Indonesian rainfall can be described by four groups based on seasonal isotopic variability (Belgaman et al, 2017). These four rainfall types correspond to the rainfall regions as defined by Aldrian and Dwi Susanto (2003).…”
Section: Controls On Rainfall 18 O At Tangga Cavementioning
confidence: 68%
“…Rainfall in central Sumatra has similar isotopic characteristics to northern Sumatra and western Borneo, consisting of two peaks each year of high δ 18 O related to seasonal migration of the ITCZ. Rainfall δ 18 O in this domain tends to show only a weak amount effect (Belgaman et al, 2017).…”
Section: Controls On Rainfall 18 O At Tangga Cavementioning
confidence: 85%
“…However, recent research has found that moisture transport/circulation (Aggarwal et al, 2012;Moore et al, 2014) and cloud type (convective vs. stratiform) (Aggarwal et al, 2016;Kurita, 2013) are also important controls on precipitation isotopes, complicating interpretations of paleo archives such as leaf waxes or speleothems. Modern water isotope studies in the IPWP hint at a more complex view of regional precipitation isotopes than the amount effect and emphasize the importance of multiple processes, including strength of regional convection, rain reevaporation, cloud types, and seasonally changing moisture source pathways (Aldrian & Susanto, 2003;Belgaman et al, 2017;Cobb et al, 2007;Griffiths et al, 2009;Konecky et al, 2016Konecky et al, , 2019Kurita et al, 2009;Moerman et al, 2013;Wurtzel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, rainfall in northwest Sumatra does not exhibit pronounced seasonality and is largely sourced locally from the Indian Ocean (Niedermeyer et al, 2014; Wu et al, 2009; Wurtzel et al, 2018). Precipitation isotope variability over this area reflects changes in moisture source and rainfall amount, with the most depleted values associated with a local Indian Ocean source (Belgaman et al, 2017; Wurtzel et al, 2018). In the southern IPWP, where rainfall is more seasonal, there is an increased regional amount effect during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…First, the spatial distributions of speleothem and rainfall δ 18 O in the Maritime Continent coincide with the distributions of large-scale convective systems and regional rainfall amount, as shown by satellite observations (Figure 2.4 and 2.5). And second, a strong correlation between rainfall δ 18 O and regional rainfall amount has been confirmed by cave monitoring studies and modern rainfall δ 18 O observations across the region, with seasonal minima of drip water and rainfall δ 18 O coinciding with the passage of the ITCZ (Belgaman et al, 2017;. On intra-seasonal timescales, anomalies of drip water/rainfall δ 18 O also commonly coincide with rainfall anomalies associated with the variability of the Madden-Julian Oscillation (MJO), with a similar relationship existing for the El Niño/Southern Oscillation (ENSO) on interannual timescales .…”
Section: The Interpretation Of Sw Sulawesi Speleothem δ 18 Omentioning
confidence: 77%